Morphologic and Radiographic Alignment Features of Feet with Insertional Achilles Tendinopathy: A Retrospective Cohort Study. Issue 4 (November 2022) - Carpenter, Melissa L.; Gu, Wanjun; Ansah-Twum, Jeremy; Zhu, Mingjie; Hunt, Kenneth J.; Myerson, Mark S.; Li, Shuyuan
Category: Hindfoot; Sports Introduction/Purpose: Insertional Achilles tendinopathy (IAT) associated with calcification and degeneration of the insertion is a common disorder. (Figure 1) Presently, there is little understanding of the etiology, pathogenesis, and biomechanics of this disease entity, although excessive tension at the Achilles insertion associated with calcaneus abnormalities have been considered a contributing factor. Multiple imaging modalities have been used to investigate a possible correlation between calcaneus morphology and IAT. However, no prognostic criteria have yet been found. The goal of this study was to evaluate the size of the calcified enlargement of the Achilles insertion using a newly developed angular measurement, pathologic Achilles insertion angle (PAIA)1 (Figures 2-3), and compare it among groups with different hindfoot and arch height alignment features. Methods: Medical records of 85 patients with symptomatic IAT were retrospectively reviewed. Weightbearing lateral Xray images were used for morphological and radiographic analysis. The PAIA was used for the morphological evaluation. It is based on a mechanism of mapping and curve fitting and represents the extent of the enlarged Achilles insertion. (Figures2-3) A lateral view of subtalar joint alignment (LVSJA), which reflects the alignment of the hindfoot (neutral, varus or valgus), the calcaneal Pitch angle, and the ratio of the Medial Cuneiform Base Height/Cuboid Height as well as the ratio of the Medial Cuneiform Base Height/Fifth Metatarsal Height, which reflect the arch height features were assessed. The comparison of PAIA among the three groups of LVSJA, as well as the correlation between PAIA and arch height ratios were also studied. Statistical analysis was performed using SAS 9.4. Results: There were 38 males and 47 females with a mean age 54.59 (range 34-80), pitch angle 21.37 degrees (range 12.18-33.20) and PAIA 12.56 degrees (range 2.45-29.79). The LVSJA showed that 59 patients had a neutral hindfoot (69.41%), 14 had a varus (16.47%), and 12 (14.12%) had a valgus hindfoot. Among these three subgroups, there were significant differences of the calcaneus Pitch angle, and the Medial Cuneiform Base Height/Cuboid Height between the valgus and varus hindfoot groups, and the valgus and neutral hindfoot groups, but not the varus and neutral hindfoot groups. No difference was found in the Medial Cuneiform Base Height/Fifth Metatarsal Height between any two of the three subgroups. The PAIA difference between the neutral and varus hindfoot groups was significantly larger than the others. There was no significant correlation between PAIA and the calcaneal Pitch angle, as well as the two arch height indexes. (Tables 1-2) Conclusion: This study is the first to include the morphology of the calcaneus, the hindfoot and arch height features of the foot in assessing symptomatic IAT. It has found that in this cohort patients with a varus hindfoot had a much smaller calcified enlargement of the Achilles insertion than those with a neutral hindfoot. Further investigation with a larger sample size to study possible correlations among clinical symptoms, calcaneus morphology, and alignment of the feet will be helpful to guide both diagnosis and treatment of IAT in particular when the patient has combined malalignment issues in the hindfoot and midfoot.